Design, Synthesis and Bioevaluation of Novel N‐Substituted‐3, 5‐Bis(Arylidene)‐4‐piperidone Derivatives as Cytotoxic and Antitumor Agents with Fluorescent Properties. (1st February 2014) - Sun, Jufeng; Zhang, Shuping; Yu, Chen; Hou, Guige; Zhang, Xiaofan; Li, Keke; Zhao, Feng
<x xml:space="preserve">Abstract</x> Ten new N‐substituted‐3, 5‐bis(arylidene)‐4‐piperidone derivatives (series 1 and 2) were synthesized and subsequently evaluated against human carcinoma cell lines SW1990, MIA PaCa‐2, PG‐BE1, NCI‐H460, and SK‐BR‐3 for cytotoxic activity by the CCK‐8 method, and their fluorescent properties were investigated as well. The compounds were confirmed to display greater cytotoxic activity to the neoplastic cells, and approximately 50% of the IC50 values were lower than 5 μm. In particular, compounds 1a, 1c, 1d, and 1e bearing 3‐bromophenyl groups were revealed as the most active antitumor drug candidates and had the average IC50 values of 1.94, 1.11, 1.16, and 0.817 μm, respectively. Furthermore, their fluorescent properties were interesting and might contribute to the visualization of their distribution in tumor cells. Some possible reasons for the disparity between cytotoxic activity and fluorescent properties in the two series of compounds were explored. This study revealed high potential of these molecules for further development as fluorescent cytotoxic and antitumor agents.